THE CATALAN SEPARATIST INTEREST IN SERBIA DURING THE FIRST WORLD WAR (1914–1919) - Joan Esculies (Istorija 20. Veka)
During the First World War, Catalan separatism established parallels between Catalonia and other European nations. Its propaganda presented a Germanophile Spain against an Alliadophile Catalonia. Separatism also encouraged young Catalans to fight in the French Foreign Legion. In this way, separatists established a syllogism: when the Allies would defeat the Central powers, they should return the aid by pressuring Spain to grant Catalonia autonomy or even independence. By presenting Catalonia as a nation or ‘state’ oppressed by Germanophile imperialism, separatist propaganda compared itself to states or nations, such as Belgium, Lithuania, the Czech Lands and Poland. But, above all, with Serbia. This article explains how Catalan separatism articulated its propaganda and the strategies used to establish the parallel between Catalonia and Serbia from the beginning of the Great War to the Paris Peace Conference and the role of the Serbian consulate from Barcelona.